Mixed crystal composition of quinacridone and diketopyrrolopyrrole and preparation method

Mixed crystals of quinacridones and 5,12-dihydroquinoline[2,3-b]acridine-7,14-dione were prepared by solvent-salt kneading process, combining diketopyrrolopyrrole and Quinacridone synergist solves the problem of poor transparency and color strength of magenta pigments in the prior art, provides high-performance chlorine-free magenta pigments, and simplifies process steps, improving stability and environmental protection.

CN119137221APending Publication Date: 2024-12-13SUN CHEMICAL CORP +1
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202380036467.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-04-26
Filing Date
2023-04-25
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

In the prior art, when preparing magenta pigments, it is difficult to meet the requirements of high transparency and high color intensity. Commonly used pigments release halogen after incineration, affecting the environment, and have many process steps and are unstable.

Method used

The solvent-salt kneading process is used to form a mixture of quinacridones and 5,12-dihydroquinoline[2,3-b]acridine-7,14-dione, and combine diketopyrrolopyrrol and quinacridone synergist to achieve a one-step process to prepare chlorine-free pigments with excellent color properties.

Benefits of technology

Achieve high transparency and high color intensity preparation of chlorine-free pigments, reduce process steps, improve product stability, and avoid halogen release, providing solutions to poor color performance and process complexity in the prior art plan.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005102176900000271
    Figure BDA0005102176900000271
Patent Text Reader

Abstract

A method of making a mixed crystal pigment composition in a one-step process by solvent-salt kneading is described. The composition may be a magenta pigment composed of a mixed crystal of two quinacridones (PV 19 and PR 122) and a physical mixture of at least one diketopyrrolopyrrole.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] The cited references do not relate to the composition of the products of the present application and do not relate to the target properties (hue, color strength, transparency). Furthermore, the references do not relate to the use of solvent-salt kneading in the production of mixed crystals and the overall composition.

[0002] All references related to producing solid solution or mixed crystal by co-synthesis require additional finishing steps (e.g., grinding, solvent refining, blending) to obtain pigment materials. A large number of processing steps need to increase production time and energy output. In addition, each processing step shows inherent responsibility with regard to process stability. By reducing the number of processing steps to a single step, the process becomes more effective, faster and less prone to product quality instability.

[0003] None of the references involve chlorine-free alternatives that are compatible with the compositions of the present application.

[0004] In most cases the printing industry uses four process colors in inks: cyan, magenta, yellow and black (CMYK). In recent years, there has been an increasing demand for halogen-free alternatives to the recognized standard pigments in order to prevent the release of halogens into the environment, for example when the printed material is incinerated at the end of its life cycle. A particular problem exists with yellowish magenta pigments, since the widely recognized pigments either contain halogen atoms (PR 48:2, PR 48:8, PR 146) or have a weak color strength (PV 19, mixed crystals of PV19 and PR 122) and therefore exhibit low use value or exhibit high opacity.

[0005] PV 19 is 5,12-dihydroquinolino[2,3-b]acridine-7,14-dione (CIPV 19, CAS 1047-16-1). PR 122 is 2,9-dimethyl-5,12-dihydroquinolino[2,3-b]acridine-7,14-dione (CIPR 122, CAS 980-26-7).

[0006] It is known that PV 19 and PR 122 can be synthesized by co-cyclization of diarylaminoterephthalic acid and dialkylarylaminoterephthalic acid in polyphosphoric acid to form mixed crystals in a ratio of 85:15-60:40. However, this co-synthesis only produces crude pigments and requires additional finishing steps to produce useful pigments (e.g. EP 3778784 A1). This method provides magenta with low color strength and / or a hue that is too blue.

[0007] Studies have shown that existing commercial mixed crystals of PV 19 and PR 122 do not meet the requirements in terms of color strength and color tone. We have surprisingly found that by forming a physical mixture of DPP (diketopyrrolopyrrole) (color index PR 264 or PR 272) and optionally a synergist (e.g. a quinacridone pigment derivative such as a monosulfonic acid metal salt derivative of PV 19) with mixed crystals of PV 19+PR122 by solvent-salt kneading, chlorine-free yellow-hued magentas with high transparency and color strength can be achieved.

[0008] PR 264 is 3,6-di-biphenyl-4-yl-2,5-dihydropyrrolo[3,4-c]pyrrole-1,4-dione (CIPR 264, CAS 88949-33-1). PR 272 is 3,6-di(4-methylphenyl)-2,5-dihydropyrrolo[3,4-c]pyrrole-1,4-dione (CIPR 272, CAS 84632-66-6).

[0009] It is well known that quinacridones can be formed into solid solutions or mixed crystals by co-synthesis in a polyphosphoric acid process or by wet milling. However, co-synthesis only produces a crude pigment and requires an additional finishing step to produce a useful pigment. In this method, particle size and morphology are difficult to control. In addition, if the co-synthesis method is implemented as in US2005011403A1 with the nucleophilic substitution of dialkyl succinyl succinate and an aniline derivative, an asymmetric QA (quinacridone) is formed, which results in the need to carry out a cumbersome global registration of CIPR 282. Additionaly, the production of solid solutions or mixed crystals by co-synthesis makes it difficult to control the specific ratio of the individual components because of the different yields of the individual synthesis.

[0010] The process according to the invention is advantageous because mixed crystals can be formed from the crude pigments of the individual components (PV 19 and PR 122) by solvent-salt kneading. Solvent-salt kneading as a comminution technique helps to reduce the particle size and at the same time enables the crystals to be regrown in a suitable solvent system. We have found that intensive mixing of the individual components is conducive to the formation of solid solutions / mixed crystals. The parameters that influence the particle size during the solvent-salt kneading process are known to those skilled in the art and can be easily adjusted to adjust the particle size of the resulting pigment and thus its properties.

[0011] In one embodiment, the crude pigment of the single components (PV 19 and PR 122) comprises a pigment of the single components (PV 19 and PR 122) obtained from a synthesis of the single components (PV 19 and PR 122), preferably obtained from a synthesis without a finishing step, wherein the finishing step preferably comprises a modification selected from the group consisting of a particle size modification and a surface modification.

[0012] For the purposes of this application, a solid solution may be defined as a crystalline material consisting of a host compound and one or more guest compounds incorporated into the host lattice. Thus, a solid solution is characterized by the host lattice. In addition, for the purposes of this application, a mixed crystal may be defined as a crystalline material consisting of two or more compounds and having a lattice different from that of the individual components (High Performance Pigments, Hugh M. Smith, ed., p. 296, Wiley-VCH Verlag-GmbH, 2002, ISBN 3-527-30204-2).

[0013] Both solid solutions and mixed crystals can be characterized, for example, by powder X-ray diffraction. In the present application, mixed crystals can be regarded as a solid solution.

[0014] The raw materials used in the solvent-salt kneading process to form the mixed crystals can be synthesized separately; therefore, no co-synthesis is required. Because the solvent-salt kneading is used as a comminution and regrowth process at the same time, there is no need to pre-grind the material and large particle raw materials can be used. Another advantage is that other components (PR 264, PR 272 or any QA (quinacridone) synergist, DPP (diketopyrrolopyrrole) synergist, resin or additive) can be easily added to the product by introducing the material into the solvent-salt kneading process before and / or during and / or after the formation of the QA (quinacridone) mixed crystals. The added materials can be easily incorporated into the product and help to adjust the color properties and secondary properties (e.g., rheology, durability) of the product. Therefore, compared with conventional methods involving several processes (grinding, solvent refining, blending, etc.), the method of the present invention is used as a one-step process.

[0015] In one embodiment, the feedstock used in the solvent-salt kneading process comprises a material obtained from a synthesis of a single material, preferably a synthesis without a finishing step, wherein the finishing step preferably comprises a modification selected from the group consisting of particle size modification and surface modification.

[0016] In another embodiment, the large particle feedstock comprises material obtained from a synthesis of a single component, preferably obtained from a synthesis without a finishing step, wherein the finishing step preferably includes a modification selected from the group consisting of particle size modification and surface modification.

[0017] Solvent-salt kneading is a highly versatile method for producing solid solutions or mixed crystals, as it can be easily adapted to different chemical reactions that do not require co-synthesis.

[0018] Solvent-salt kneading simultaneously promotes the formation of solid solutions or mixed crystals and the finishing of the material by comminution and regrowth to the optimum particle size and distribution. Thus, solvent-salt kneading is a one-step process (mixed crystal formation + finishing step) compared to the prior art multi-step processes that require mixed crystal formation and subsequent milling, finishing, blending steps.

[0019] The pigments refined in this one-step procedure present a more uniform particle size for both the mixed crystal and physical mixture components and therefore present equal or very similar dispersion properties for each of its components. This is highly advantageous for tinting compared to paints / inks prepared with several components blended in a mill base (e.g. EP 3480264 B1).

[0020] The composition of the present invention distinguishes itself from the industry standard because it is a halogen-free pale yellow magenta with excellent color strength and clarity. Other commercially available pigments cannot match these properties.

[0021] Citation or identification of any document in this application is not an admission that such document represents prior art to the present invention.

[0022] The present application describes a one-step solvent-salt kneading process for preparing a magenta pigment consisting of mixed crystals of two quinacridones (PV 19 and PR 122). In the resulting composition, the magenta pigment further comprises a physical mixture with at least one diketopyrrolopyrrole (Pigment Red 264 and Pigment Red 272) in a ratio of 60:40-85:15 or 60:40-75:25, accounting for 1-15% or 4-10% by weight of the entire composition. In addition, the composition may optionally include 0-15% of a quinacridone synergist, such as a monosulfonic acid metal salt derivative of PV 19. The composition is advantageously manufactured in a one-step process by solvent-salt kneading.

[0023] Yellow-toned magentas ("process red" colors) mainly constitute azo pigments (e.g. PR 57:1; PR 48:2; PR146, PR 269) which are known to be unable to match the excellent properties of high-performance pigments such as quinacridones or diketopyrrolopyrroles. Moreover, of the azo pigments mentioned, only PR 57:1 is chlorine-free. Thus, the compositions of the present application formed by the solvent-salt kneading process offer a unique chlorine-free, high-performance alternative to azo pigments in the field of "process red" colors for printing applications. Quinacridone-based magentas such as PV 19 or mixed crystals of PV 19 and PR 122 are chlorine-free and are considered high-performance pigments, but do not meet the requirements regarding hue, transparency and color strength.

[0024] In the present invention, the quinacridone mixed crystal means a quinacridone mixed crystal containing PV 19 and PR 122 as essential components; more specifically, a quinacridone solid solution in which a mixed crystal phase of PR 122 and PV 19 is formed. Therefore, the mixed crystal has inherent peaks at 5.9°±0.2°2θ and 11.9°±0.2° diffraction angles measured by powder X-ray diffraction, which peaks do not exist in any of the single crystals of PV 19 and the single crystals of PR 122. Therefore, it can be easily detected by crystal X-ray diffraction whether the quinacridone pigment is a mixed crystal or a mixture of single crystals only.

[0025] The composition of the present application further contains PR 264 or PR 272 and, if applicable, a quinacridone synergist, such as a monosulfonic acid metal salt derivative of PV 19, in a physical mixture with the above-mentioned mixed crystals. The presence of either can be found, for example, by mass spectrometry.

[0026] The compositions according to the invention can advantageously be prepared by solvent-salt kneading which promotes the formation of quinacridone mixed crystals by intensive mixing during the continuous comminution and regrowth in the process.

[0027] Solvent-salt kneading is carried out with an organic solvent, for example one or more of ethylene glycol, diethylene glycol, diacetone alcohol, dimethylformamide, glycerol, triethylene glycol, dipropylene glycol, ethylene glycol monobutyl ether, methyl ethyl ketone, cyclohexanone, dimethylacetamide, N-methylpyrrolidone, butyl acetate, glycerol triacetate, sulfolane, xylene, tetrahydrofuran, butanol, water and dimethyl sulfoxide. In one embodiment, the at least one solvent comprises one or more of diethylene glycol, diacetone alcohol and glycerol. In one embodiment, the at least one solvent is diethylene glycol.

[0028] In one embodiment, the present invention includes the optional addition of one or more quinacridone synergists, such as sulfonic acid derivatives and / or salts of quinacridone; reaction products of formaldehyde with 5,12-dihydroquinolino[2,3-b]acridine-7,14-dione and 3,5-dimethyl-1H-pyrazole; sulfonated reaction products of formaldehyde with 5,12-dihydroquinolino[2,3-b]acridine-7,14-dione and 3,5-dimethyl-1H-pyrazole or 2-[(1,3-dihydro-1,3-dioxo-2H-isoindol-2-yl)methyl]-5,12-dihydroquinolino[2,3-b]acridine-7,14-dione.

[0029] In one embodiment, the present invention includes the optional addition of one or more synergists, such as natural or synthetic resins containing esters and salts of abietic acid; hydrated or partially hydrogenated or dimerized rosins; polysorbate-type nonionic surfactants containing esters or ester mixtures formed from fatty acids such as lauric acid or sebacic acid; and polyols such as sorbitan monolaurate or dibutyl sebacate. The synergist can be added before and / or during and / or after kneading and / or grinding.

[0030] In the powder X-ray diffraction pattern, the mixed crystal of PR 122 and PV 19 has two signals at 5.9°±0.2°2θ and 11.9°±0.2°2θ, which are not present in the diffraction patterns of the individual components and are not present in the crystal lattice of typical commercial PR 122 solid solutions, such as Hostaperm Pink E (Heubach). These signals are well separated from the other signals in the diffraction pattern and are therefore ideal for characterizing the mixed crystal.

[0031] The successful formation of mixed crystals can be evaluated by the intensity ratio of the two signals.

[0032] Intensity ratio=(diffraction peak intensity at a diffraction angle 2θ of about 5.9°) / (diffraction peak intensity at a diffraction angle 2θ of about 11.9°)>3.

[0033] As described, when the DPP (diketopyrrolopyrrole) component is added to the solvent-salt kneading of the QA (quinacridone) mixed crystals, a physical mixture between the mixed crystals and the DPP (diketopyrrolopyrrole) is formed. This is confirmed by PXRD (powder X-ray diffraction), because the diffraction pattern is similar to the superposition of the diffraction pattern of the QA (quinacridone) mixed crystals with the diffraction pattern of the individual DPP components. Exemplarily, this can be seen by additional signals at 8.0°±0.2°2θ and 17.9°±0.2°2θ (PR 264) or 7.7°±0.2°2θ and 15.7°±0.2°2θ (PR 272) when it is added.

[0034] Solvent-salt kneading uses an inorganic salt as a grinding medium, such as sodium chloride, sodium sulfate or anhydrous aluminum sulfate or a mixture thereof. In one embodiment, the pigment / salt ratio is 1:3-1:18; in another embodiment, 1:4-1:12; in another embodiment, 1:6-1:8. Solvent-salt kneading is advantageously carried out at a temperature of 25-120° C., such as 40-100° C. or 60-80° C. Solvent-salt kneading is generally carried out for 4-48 hours, such as 6-24 hours or 8-18 hours.

[0035] During the solvent-salt kneading process, the pigment is formed as crystalline particles with a particle size Dv(50) <150 nm. Preferably, the pigment has a particle size distribution Dv(50) in the range of 10-145 nm, more preferably 20-140 nm, more preferably 25-130 nm, more preferably 30-120 nm. The individual coarse components can have significantly larger particle sizes and still give products with excellent color properties.

[0036] According to the method of the present invention, the mixed crystal quinacridone pigment composition has a particle size distribution Dv(50) <150 nm, preferably the mixed crystal quinacridone pigment composition has a particle size distribution Dv(50) within the range of 10-145 nm, more preferably 20-140 nm, more preferably 25-130 nm, more preferably 30-120 nm as measured according to Reference Example 5.

[0037] Furthermore, according to the process of the present invention, the process further comprises grinding the crude quinacridone pigment in the presence of a diketopyrrolopyrrole selected from the group consisting of PR 264, PR 272 and mixtures thereof.

[0038] According to the process of the present invention, PV 19 is 5,12-dihydroquinolino[2,3-b]acridine-7,14-dione and / or PR 122 is 2,9-dimethyl-5,12-dihydroquinolino[2,3-b]acridine-7,14-dione and / or PR 264 is 3,6-di-biphenyl-4-yl-2,5-dihydropyrrolo[3,4-c]pyrrole-1,4-dione and / or PR 272 is 3,6-di(4-methylphenyl)-2,5-dihydropyrrolo[3,4-c]pyrrole-1,4-dione.

[0039] According to the method of the present invention, the one-step solvent-salt kneading process is a solvent-salt kneading process.

[0040] According to the process of the present invention, in (a) the crude quinacridone pigment comprises a pigment obtained from the synthesis of the quinacridone pigment, preferably from a synthesis without a finishing step, wherein the finishing step preferably comprises a modification selected from particle size modification and surface modification.

[0041] According to the process of the present invention, in (a) the temperature is in the range of 60-90°C, preferably 40-90°C, more preferably 80-90°C or the temperature is in the range of 45-100°C, preferably 50-90°C.

[0042] According to the process of the present invention, in (a)(i), the inorganic salt is selected from alkali metal halides, alkali metal sulfates, alkaline earth metal halides, alkaline earth metal sulfates and mixtures of two or more thereof, preferably the inorganic salt is selected from sodium chloride, sodium sulfate, anhydrous aluminum sulfate and mixtures of two or more thereof, more preferably the inorganic salt is sodium chloride.

[0043] According to the process of the present invention, in (a)(ii) at a temperature in the range of 20-25°C, the solubility of the crude quinacridone pigment and the salt in the organic liquid is in the range of 0-10 g / L, preferably 0.0001-9.5 g / L, more preferably 0.0005-9 g / L.

[0044] The method of any preceding paragraph, wherein in (a)(ii) the salt comprises an inorganic salt.

[0045] According to the method of the present invention, the mixed crystal quinacridone pigment composition comprises a quinacridone synergist, wherein 0-10 wt % of the mixed crystal quinacridone pigment composition is constituted by the quinacridone synergist.

[0046] According to the method of the present invention, the particle size distribution Dv(50) is determined according to Reference Example 5.

[0047] According to the process of the present invention, in (c) the quinacridone pigment has a particle size distribution Dv(50) measured according to Reference Example 5 in the range of 10-145 nm, preferably 20-140 nm, more preferably 25-130 nm, more preferably 30-120 nm.

[0048] According to the process of the present invention, in (a)(ii) the organic liquid comprises a solvent.

[0049] In one embodiment, the crude fraction comprises a fraction obtained in the synthesis of a single fraction, preferably obtained from a synthesis without a finishing step, wherein the finishing step preferably comprises a modification selected from the group consisting of particle size modification and surface modification.

[0050] The invention is further illustrated by the following numbered paragraphs, which represent a set of embodiments and combinations of embodiments resulting from the indicated dependencies and back-references. It should be noted in particular that in each case where a range of embodiments is mentioned, for example in the context of a term such as "a process according to any one of embodiments 1-5", each embodiment within the range is intended to be explicitly disclosed to the skilled person, i.e. the wording of the term should be understood by the skilled person as being synonymous with "a process according to any one of embodiments 1, 2, 3, 4 and 5". Furthermore, it should be explicitly noted that the following set of embodiments is not the set of claims that determines the scope of protection, but represents a suitable structural part of the description relating to general and preferred aspects of the invention.

[0051] 1. A method for preparing a mixed crystal quinacridone pigment composition, comprising a one-step solvent-salt kneading process, the method comprising the following steps:

[0052] (a) at a temperature in the range of about 40-120°C or 60-90°C or 40-90°C or 80-90°C under

[0053] The crude quinacridone pigment is ground in the presence of the following substances:

[0054] (i) an inorganic salt in the range of about 3 to 12 parts by weight relative to the crude quinacridone pigment;

[0055] (ii) an organic liquid in which the crude quinacridone pigment and salt are substantially insoluble; and

[0056] (iii) optionally, a quinacridone synergist;

[0057] (b) discharging the crude quinacridone pigment from step (a) into water; thereby obtaining a water / pigment mixture; and

[0058] (c) separating a quinacridone pigment having a particle size distribution Dv(50) <150 nm from the mixture.

[0059] 2. The method of paragraph 1, wherein the composition comprises a combination of PV 19 and PR 122, preferably wherein the composition is a combination of PV 19 and PR 122.

[0060] 3. The method of paragraph 2, further comprising a diketopyrrolopyrrole selected from PR 264, PR 272 or both in the range of 0.1-15 wt % or 1-15 wt % or 5-10 wt % based on the total composition.

[0061] 4. The method of paragraph 2, wherein the PV 19 and PR 122 are present in a ratio of 60:40-85:15 or 60:40-75:25.

[0062] 5. The method of any preceding paragraph, wherein the mixed crystal quinacridone pigment composition has a particle size distribution Dv(50) <150 nm as measured according to Reference Example 5, preferably the mixed crystal quinacridone pigment composition has a particle size distribution Dv(50) in the range of 10-145 nm, more preferably 20-140 nm, more preferably 25-130 nm, more preferably 30-120 nm.

[0063] 6. The process of any preceding paragraph, wherein (a) further comprises grinding the crude quinacridone pigment in the presence of a diketopyrrolopyrrole selected from the group consisting of PR 264, PR 272, and mixtures thereof.

[0064] 7. The process of any preceding paragraph, wherein PV 19 is 5,12-dihydroquinolino[2,3-b]acridine-7,14-dione and / or PR 122 is 2,9-dimethyl-5,12-dihydroquinolino[2,3-b]acridine-7,14-dione and / or PR 264 is 3,6-di-biphenyl-4-yl-2,5-dihydropyrrolo[3,4-c]pyrrole-1,4-dione and / or PR 272 is 3,6-di(4-methylphenyl)-2,5-dihydropyrrolo[3,4-c]pyrrole-1,4-dione.

[0065] 8. The process of any preceding paragraph, wherein the one-step solvent-salt kneading process is a solvent-salt kneading process.

[0066] 9. The method of any preceding paragraph, wherein in (a) the crude quinacridone pigment comprises a pigment obtained from a synthesis of the quinacridone pigment, preferably a synthesis without a finishing step, wherein the finishing step preferably comprises a modification selected from the group consisting of particle size modification and surface modification.

[0067] 10. The process of any preceding paragraph, wherein in (a) the temperature is in the range of 60-90°C, preferably 40-90°C, more preferably 80-90°C or the temperature is in the range of 45-100°C, preferably 50-90°C.

[0068] 11. The method of any preceding paragraph, wherein in (a)(i) the inorganic salt is selected from alkali metal halides, alkali metal sulfates, alkaline earth metal halides, alkaline earth metal sulfates and mixtures of two or more thereof, preferably wherein the inorganic salt is selected from sodium chloride, sodium sulfate, anhydrous aluminum sulfate and mixtures of two or more thereof, more preferably wherein the inorganic salt is sodium chloride.

[0069] 12. The process of any preceding paragraph, wherein in (a)(ii) the solubility of the crude quinacridone pigment and the salt in the organic liquid at a temperature in the range of 20-25°C is in the range of 0-10 g / L, preferably 0.0001-9.5 g / L, more preferably 0.0005-9 g / L.

[0070] 13. The method of any preceding paragraph, wherein in (a)(ii) the salt comprises an inorganic salt.

[0071] 14. The method of any preceding paragraph, wherein the mixed crystal quinacridone pigment composition comprises a quinacridone synergist, wherein 0-10 weight percent of the mixed crystal quinacridone pigment composition consists of the quinacridone synergist.

[0072] 15. The method of any preceding paragraph, wherein the particle size distribution Dv(50) is determined according to Reference Example 5.

[0073] 16. The process of any preceding paragraph, wherein in (c) the quinacridone pigment has a particle size distribution Dv(50) determined according to Reference Example 5 in the range of 10-145 nm, preferably 20-140 nm, more preferably 25-130 nm, more preferably 30-120 nm.

[0074] 17. The method of any preceding paragraph, wherein in (a)(ii) the organic liquid comprises a solvent.

[0075] 18. The process of any preceding paragraph, comprising a solvent selected from the group consisting of ethylene glycol, diethylene glycol, diacetone alcohol, dimethylformamide, glycerol, triethylene glycol, dipropylene glycol, ethylene glycol monobutyl ether, methyl ethyl ketone, cyclohexanone, dimethylacetamide, N-methylpyrrolidone, butyl acetate, glycerol triacetate, sulfolane, xylene, tetrahydrofuran, butanol, water, dimethyl sulfoxide, and blends thereof, preferably the solvent is selected from the group consisting of ethylene glycol, diethylene glycol, diacetone alcohol, dimethylformamide, glycerol, triethylene glycol, dipropylene glycol, ethylene glycol monobutyl ether, methyl ethyl ketone, cyclohexanone, dimethylacetamide, N-methylpyrrolidone, butyl acetate, glycerol triacetate, sulfolane, xylene, tetrahydrofuran, dimethyl sulfoxide, and mixtures of two or more thereof.

[0076] 19. The method of paragraph 18, wherein the at least one solvent comprises one or more of diethylene glycol, diacetone alcohol and glycerol, preferably the solvent is diethylene glycol.

[0077] 20. The method of any preceding paragraph, wherein the synergist is a quinacridone derivative selected from the group consisting of quinacridone sulfonic acid and its salts, phthalimidoalkyl-quinacridones, imidazolylalkyl-quinacridones, pyrazolylalkyl-quinacridones, sulfonic acids and salts of pyrazolylalkyl-quinacridones and dialkylaminoalkylsulfonamide derivatives of quinacridones.

[0078] 21. The method of any preceding paragraph, wherein the synergist is selected from the group consisting of sulfonic acid derivatives and / or salts of quinacridone; 5,7,12,14-tetrahydro-7,14-dioxoquinolino[2,3-b]acridine-2-sulfonic acid and its metal salts; the reaction product of formaldehyde with 5,12-dihydroquinolino[2,3-b]acridine-7,14-dione and 3,5-dimethyl-1H-pyrazole; the reaction product of formaldehyde with 5,12-dihydroquinolino[2,3-b]acridine-7,14-dione and 3,5-dimethyl-1H-pyrazole. Sulfonated reaction products of pyrazole or 2-[(1,3-dihydro-1,3-dioxo-2H-isoindol-2-yl)methyl]-5,12-dihydroquinolino[2,3-b]acridine-7,14-dione; natural or synthetic resins containing esters and salts of abietic acid; hydrated or partially hydrogenated or dimerized rosins; polysorbate-type nonionic surfactants containing esters or ester mixtures formed from fatty acids such as lauric acid or sebacic acid; polyols such as sorbitan monolaurate or dibutyl sebacate; and blends thereof.

[0079] 22. The method of any preceding paragraph, wherein the synergist is present in an amount of 1-10 wt % relative to the crude quinacridone pigment, preferably the synergist in (a)(iii) is present in an amount of 1-10 wt % relative to the crude quinacridone pigment in (a).

[0080] 23. The method of any preceding paragraph, wherein the synergist is present in an amount of 1-5 wt % relative to the crude quinacridone pigment, preferably the synergist in (a)(iii) is present in an amount of 1-5 wt % relative to the crude quinacridone pigment in (a).

[0081] 24. The method of any preceding paragraph, wherein the synergist is present in the range of about 0.001-0.1 parts by weight relative to the crude quinacridone pigment, preferably the synergist in (a)(iii) is present in the range of about 0.001-0.1 parts by weight relative to the crude quinacridone pigment in (a).

[0082] 25. The process of any preceding paragraph, wherein the narrow particle size distribution obtained as Dv(50) is determined according to Reference Example 5 to be <150 nm, preferably the narrow particle size distribution obtained as Dv(50) is in the range of 10-145 nm, more preferably 20-140 nm, more preferably 25-130 nm, more preferably 30-120 nm.

[0083] 26. The method of any preceding paragraph, wherein the composition is characterized by powder X-ray diffraction signals at diffraction angles 2θ of about 5.9°±0.2° and 11.9°±0.2°.

[0084] 27. The method of paragraph 26, wherein the composition is further characterized by powder X-ray diffraction signals at diffraction angles of 8.0°±0.2°2θ and 17.9°±0.2°2θ after addition of PR 264.

[0085] 28. The method of paragraph 26, wherein the composition is further characterized by powder X-ray diffraction signals at diffraction angles of 7.7°±0.2° 2θ and 15.7°±0.2° 2θ after addition of PR 272.

[0086] 29. A mixed crystal quinacridone pigment composition obtained by the method of any one of paragraphs 1-28.

[0087] 30. The pigment composition of paragraph 29, wherein the ratio of the diffraction peak intensity at a diffraction angle 2θ of 5.9±0.2° to the diffraction peak intensity at a diffraction angle 2θ of 11.9±0.2°C is 3 or more as measured by a powder X-ray diffraction method, preferably the ratio of the diffraction peak intensity at a diffraction angle 2θ of 5.9±0.2° to the diffraction peak intensity at a diffraction angle 2θ of 11.9±0.2°C is in the range of 3 to 20, more preferably 6 to 10, and preferably the ratio of the diffraction peak intensities is measured according to Reference Example 4.

[0088] 31. The pigment composition of paragraph 29 or 30, wherein the content of the quinacridone pigment derivative is 0.1 to 10 parts by mass relative to 100 parts by mass of the pigment, preferably the amount of the quinacridone pigment derivative contained in (a)(iii) is 0.1 to 10 parts by mass relative to 100 parts by mass of the mixed crystal quinacridone pigment composition.

[0089] 32. The pigment composition of paragraph 29 or 30, wherein the content of the quinacridone pigment derivative is 1 to 5 parts by mass relative to 100 parts by mass of the pigment, and preferably the amount of the quinacridone pigment derivative contained in (a)(iii) is 1 to 5 parts by mass relative to 100 parts by mass of the mixed crystal quinacridone pigment composition.

[0090] 33. The pigment composition of paragraph 29 or 30, wherein the content of the quinacridone pigment derivative is 0.5-3 parts by mass, preferably 1-3 parts by mass, relative to 100 parts by mass of the pigment, and preferably the amount of the quinacridone pigment derivative contained in (a)(iii) is 0.5-3 parts by mass, preferably 1-3 parts by mass, relative to 100 parts by mass of the mixed crystal quinacridone pigment composition.

[0091] 34. The pigment composition of any of paragraphs 29-33, wherein the narrow particle size distribution obtained as Dv(50) is determined according to Reference Example 5 to be <150 nm, preferably the narrow particle size distribution obtained as Dv(50) is in the range of 10-145 nm, more preferably 20-140 nm, more preferably 25-130 nm, more preferably 30-120 nm.

[0092] 35. The pigment composition of any of paragraphs 29-34, wherein the composition is chlorine-free.

[0093] 36. A printing ink or coating or plastic composition comprising the pigment composition of any one of paragraphs 29 to 35.

[0094] 37. The printing ink or coating composition of paragraph 36, wherein the composition is suitable for use as a printing ink, automotive coating, architectural coating or industrial coating.

[0095] 38. The printing ink composition of paragraph 37, wherein the composition is suitable for use as a digital printing ink, an inkjet ink, an electrophotographic toner, an aqueous ink, a UV curable ink, a solvent-based ink or an oil-based ink.

[0096] 39. A printed or coated article comprising the printing ink or coating composition of any of paragraphs 35-38.

[0097] 40. The printed article of paragraph 39, wherein the article is a plastic article.

[0098] 41. A plastic article comprising the pigment composition of any of paragraphs 29-35.

[0099] Furthermore, the present invention relates to a method for producing a mixed crystal quinacridone pigment composition, the method comprising:

[0100] (a) grinding at least two quinacridones at a temperature in the range of 40-120°C in the presence of

[0101] pigment:

[0102] (i) an inorganic salt in an amount ranging from 3 to 12 parts by weight based on the at least two quinacridone pigments;

[0103] (ii) an organic liquid selected from the group consisting of ethylene glycol, diethylene glycol, diacetone alcohol, dimethylformamide, glycerol, triethylene glycol, dipropylene glycol, ethylene glycol monobutyl ether, methyl ethyl ketone, cyclohexanone, dimethylacetamide, N-methylpyrrolidone, butyl acetate, glycerol triacetate, sulfolane, xylene, tetrahydrofuran, dimethyl sulfoxide, and a mixture of two or more thereof; and

[0104] (iii) 0 to 10% by weight of a synergist, based on the mixed crystal quinacridone pigment composition;

[0105] (b) discharging the ground at least two quinacridone pigments from step (a) into water; and

[0106] (c) separating the at least two quinacridone pigments ground from step (b);

[0107] The at least two quinacridone pigments ground have a particle size distribution Dv(50) in the range of 10-145 nm.

[0108] Preferably, the mixed crystal quinacridone pigment composition comprises PV 19 and PR 122.

[0109] Preferably, the at least two quinacridone pigments comprise PV19 and PR122.

[0110] Preferably, PV 19 and PR 122 are present in a ratio of 60:40-85:15 or 60:40-75:25.

[0111] Preferably, PV 19 is 5,12-dihydroquinolino[2,3-b]acridine-7,14-dione and / or PR 122 is 2,9-dimethyl-5,12-dihydroquinolino[2,3-b]acridine-7,14-dione.

[0112] Preferably, the process further comprises a diketopyrrolopyrrole selected from PR 264, PR 272 and mixtures thereof, wherein preferably PR 264 is 3,6-di-biphenyl-4-yl-2,5-dihydropyrrolo[3,4-c]pyrrole-1,4-dione and PR 272 is 3,6-di(4-methylphenyl)-2,5-dihydropyrrolo[3,4-c]pyrrole-1,4-dione.

[0113] In case where the process further comprises a diketopyrrolopyrrole, the amount of the diketopyrrolopyrrole is in the range of 0.1-15% by weight, preferably 1-15% by weight, more preferably 5-10% by weight, based on the mixed crystal quinacridone pigment composition.

[0114] Preferably, in (a), the at least two quinacridone pigments comprise at least two crude quinacridone pigments, wherein the at least two crude pigments comprise at least two quinacridone pigments obtained from a synthesis of the at least two quinacridone pigments, preferably obtained from a synthesis without a finishing step, wherein the finishing step preferably comprises a modification selected from particle size modification and surface modification.

[0115] Preferably in (a) the temperature is in the range of 60-90°C, preferably 40-90°C, more preferably 80-90°C or the temperature is in the range of 45-100°C, preferably 50-90°C.

[0116] Preferably, in (a)(i), the inorganic salt is selected from alkali metal halides, alkali metal sulfates, alkaline earth metal halides, alkaline earth metal sulfates and mixtures of two or more thereof, preferably wherein the inorganic salt is selected from sodium chloride, sodium sulfate, anhydrous aluminum sulfate and mixtures of two or more thereof, more preferably wherein the inorganic salt is sodium chloride.

[0117] Preferably, in (a), the at least two quinacridone pigments and the inorganic salt are substantially insoluble in the organic liquid, preferably wherein the solubility of the at least two quinacridone pigments and the inorganic salt in the organic liquid at a temperature in the range of 20-25° C. is in the range of 0-10 g / L, preferably 0.0001-9.5 g / L, more preferably 0.0005-9 g / L.

[0118] The solubility of the at least two quinacridone pigments is determined by methods known to the skilled worker.

[0119] The preferred particle size distribution Dv(50) is determined according to Reference Example 5.

[0120] Preferably, the ground at least two quinacridone pigments have a particle size distribution Dv(50) determined according to Reference Example 5 in the range of 20-140 nm, preferably 25-130 nm, more preferably 30-120 nm.

[0121] Preferably, the mixed crystal quinacridone pigment composition has a particle size distribution Dv(50) of <150 nm as measured according to Reference Example 5, preferably the mixed crystal quinacridone pigment composition has a particle size distribution Dv(50) in the range of 10-145 nm, more preferably 20-140 nm, more preferably 25-130 nm, more preferably 30-120 nm.

[0122] Preferably (a) further comprises grinding the crude quinacridone pigment in the presence of a diketopyrrolopyrrole selected from the group consisting of PR 264, PR 272 and mixtures thereof.

[0123] Preferably, the organic liquid is selected from diethylene glycol, glycerol, diacetone alcohol and a mixture of two or more thereof, preferably the organic liquid is diethylene glycol.

[0124] Preferably, the synergist in (a)(iii) is a quinacridone derivative selected from the group consisting of quinacridone sulfonic acid and its salts, phthalimidoalkyl-quinacridones, imidazolylalkyl-quinacridones, pyrazolylalkyl-quinacridones, sulfonic acids and salts of pyrazolylalkyl-quinacridones, dialkylaminoalkylsulfonamide derivatives of quinacridones and mixtures of two or more thereof.

[0125] In the case where the synergist in (a)(iii) is a quinacridone derivative, the quinacridone derivative is selected from the group consisting of sulfonic acid derivatives and / or salts of quinacridone; 5,7,12,14-tetrahydro-7,14-dioxoquinolino[2,3-b]acridine-2-sulfonic acid and its metal salts; the reaction of formaldehyde with 5,12-dihydroquinolino[2,3-b]acridine-7,14-dione and 3,5-dimethyl-1H-pyrazole; The sulfonation reaction product of formaldehyde with 5,12-dihydroquinoline [2,3-b] acridine-7,14-dione and 3,5-dimethyl-1H-pyrazole or 2-[(1,3-dihydro-1,3-dioxo-2H-isoindol-2-yl)methyl]-5,12-dihydroquinoline [2,3-b] acridine-7,14-dione and a mixture of two or more thereof, preferably the quinacridone derivative is a monosulfonic acid metal salt derivative of PV 19.

[0126] It is further preferred that the synergist in (a)(iii) is selected from natural or synthetic resins comprising esters and salts of abietic acid; hydrated or partially hydrogenated or dimerized rosins; polysorbate-type nonionic surfactants comprising esters or ester mixtures formed from fatty acids, preferably lauric acid or sebacic acid; polyols, preferably sorbitan monolaurate and dibutyl sebacate; and mixtures of two or more thereof.

[0127] Preferably the synergist in (a)(iii) is present in an amount of 1-10 wt. % based on the at least two quinacridone pigments in (a), preferably 1-5 wt. % based on the at least two quinacridone pigments in (a).

[0128] Preferably, the synergist in (a)(iii) is present in the range of 0.001 to 0.1 parts by weight based on the at least two quinacridone pigments in (a).

[0129] Preferably, the mixed crystal quinacridone pigment composition comprising the at least two quinacridone pigments has a particle size distribution Dv(50) measured according to Reference Example 5 in the range of 10-145 nm, preferably 20-140 nm, more preferably 25-130 nm, more preferably 30-120 nm.

[0130] Preferably, the mixed crystal quinacridone pigment composition is characterized by powder X-ray diffraction signals at diffraction angles 2θ of 5.9°±0.2° and 11.9°±0.2°.

[0131] Preferably, the mixed crystal quinacridone pigment composition is further characterized by powder X-ray diffraction signals after addition of PR 264 at diffraction angles 2θ of 8.0°±0.2° and 17.9°±0.2°.

[0132] Preferably, the mixed crystal quinacridone pigment composition is further characterized by powder X-ray diffraction signals after addition of PR 272 at diffraction angles 2θ of 7.7°±0.2° and 15.7°±0.2°.

[0133] Preferably the process comprises a one-step solvent-salt kneading process.

[0134] The present invention also relates to a mixed crystalline quinacridone pigment composition obtainable or obtainable according to the process of any one of the particular and preferred embodiments of the present invention for producing a mixed crystalline quinacridone pigment composition.

[0135] Preferably, the mixed crystal quinacridone pigment composition has a ratio of diffraction peak intensity at a diffraction angle 2θ of 5.9±0.2° to the diffraction peak intensity at a diffraction angle 2θ of 11.9±0.2°C as measured by powder X-ray diffraction of 3 or more, preferably, the ratio of the diffraction peak intensity at a diffraction angle 2θ of 5.9±0.2° to the diffraction peak intensity at a diffraction angle 2θ of 11.9±0.2°C is in the range of 3-20, more preferably 6-10, and preferably the ratio of the diffraction peak intensities is measured according to Reference Example 4 described herein.

[0136] Preferably, the synergist amount of the mixed crystal quinacridone pigment composition is in the range of 0.1-10 parts by mass, preferably 0.5-3 parts by mass or 1-5 parts by mass, relative to 100 parts by mass of the mixed crystal quinacridone pigment composition.

[0137] Preferably, the mixed crystal quinacridone pigment composition has a particle size distribution Dv(50) in the range of 10-145 nm, preferably 20-140 nm, more preferably 25-130 nm, more preferably 30-120 nm, as determined according to Reference Example 5 described herein.

[0138] Preferably, the mixed crystal quinacridone pigment composition is chlorine-free.

[0139] The present invention also relates to a printing ink or coating or plastic composition comprising the mixed crystal quinacridone pigment composition of any one of the specific and preferred embodiments of the present invention. Preferably, the printing ink or coating composition of the present invention is suitable for use as a printing ink, automotive coating, architectural coating or industrial coating. Preferably, the printing ink composition of the present invention is suitable for use as a digital printing ink, inkjet ink, electrophotographic toner, aqueous ink, UV curable ink, solvent-based ink or oil-based ink.

[0140] The present invention also relates to a printed or coated article comprising the printing ink or coating composition according to any one of the specific and preferred embodiments of the present invention. Preferably, the printed article is a plastic article.

[0141] The present invention also relates to a plastic article comprising the mixed crystal quinacridone pigment composition according to any one of the specific and preferred embodiments of the present invention.

[0142] The invention is further illustrated by the following set of embodiments and combinations of embodiments resulting from the indicated dependencies and back-references. In particular, it should be noted that in each case where a range of embodiments is mentioned, for example in the context of a term such as "a method according to any one of embodiments 1-4", each embodiment within the range is intended to be explicitly disclosed to the skilled person, i.e. the wording of the term should be understood by the skilled person as being synonymous with "a method according to any one of embodiments 1, 2, 3 and 4". Furthermore, it should be explicitly noted that the following set of embodiments represents a suitable structural part of a general description relating to preferred aspects of the invention and therefore properly supports but does not represent the claims of the invention.

[0143] 1. A method for preparing a mixed crystal quinacridone pigment composition, the method comprising:

[0144] (a) grinding at least two quinacridones at a temperature in the range of 40-120°C in the presence of

[0145] pigment:

[0146] (i) an inorganic salt in an amount ranging from 3 to 12 parts by weight based on the at least two quinacridone pigments;

[0147] (ii) an organic liquid selected from the group consisting of ethylene glycol, diethylene glycol, diacetone alcohol, dimethylformamide, glycerol, triethylene glycol, dipropylene glycol, ethylene glycol monobutyl ether, methyl ethyl ketone, cyclohexanone, dimethylacetamide, N-methylpyrrolidone, butyl acetate, glycerol triacetate, sulfolane, xylene, tetrahydrofuran, dimethyl sulfoxide, and a mixture of two or more thereof; and

[0148] (iii) 0 to 10% by weight of a synergist, based on the mixed crystal quinacridone pigment composition;

[0149] (b) discharging the ground at least two quinacridone pigments from step (a) into water; and

[0150] (c) separating the at least two quinacridone pigments ground from step (b);

[0151] The at least two quinacridone pigments ground have a particle size distribution Dv(50) in the range of 10-145 nm.

[0152] 2. The method of embodiment 1, wherein the mixed crystal quinacridone pigment composition comprises PV 19 and PR 122.

[0153] 3. The method of embodiment 1 or 2, wherein the at least two quinacridone pigments comprise PV 19 and PR 122.

[0154] 4. The method of embodiment 2 or 3, wherein PV 19 and PR 122 are present in a ratio of 60:40-85:15 or 60:40-75:25.

[0155] 5. The process according to any one of embodiments 2 to 4, wherein PV 19 is 5,12-dihydroquinolino[2,3-b]acridine-7,14-dione and / or PR 122 is 2,9-dimethyl-5,12-dihydroquinolino[2,3-b]acridine-7,14-dione.

[0156] 6. The method according to any one of embodiments 1 to 5, further comprising a diketopyrrolopyrrole selected from PR 264, PR 272 and mixtures thereof, wherein preferably PR 264 is 3,6-di-biphenyl-4-yl-2,5-dihydropyrrolo[3,4-c]pyrrole-1,4-dione and PR 272 is 3,6-di(4-methylphenyl)-2,5-dihydropyrrolo[3,4-c]pyrrole-1,4-dione.

[0157] 7. The process of embodiment 6, wherein the amount of the diketopyrrolopyrrole is in the range of 0.1-15% by weight, preferably 1-15% by weight, more preferably 5-10% by weight, based on the mixed crystal quinacridone pigment composition.

[0158] 8. The method of any one of embodiments 1 to 7, wherein in (a) the at least two quinacridone pigments comprise at least two crude quinacridone pigments, wherein the at least two crude pigments comprise at least two quinacridone pigments obtained from a synthesis of the at least two quinacridone pigments, preferably obtained from a synthesis without a finishing step, wherein the finishing step preferably comprises a modification selected from the group consisting of particle size modification and surface modification.

[0159] 9. The process according to any one of embodiments 1 to 8, wherein in (a) the temperature is in the range of 60-90°C, preferably 40-90°C, more preferably 80-90°C or the temperature is in the range of 45-100°C, preferably 50-90°C.

[0160] 10. The method of any one of embodiments 1 to 9, wherein in (a)(i) the inorganic salt is selected from alkali metal halides, alkali metal sulfates, alkaline earth metal halides, alkaline earth metal sulfates and mixtures of two or more thereof, preferably wherein the inorganic salt is selected from sodium chloride, sodium sulfate, anhydrous aluminum sulfate and mixtures of two or more thereof, more preferably wherein the inorganic salt is sodium chloride.

[0161] 11. The method of any one of embodiments 1-10, wherein in (a) the at least two quinacridone pigments and the inorganic salt are substantially insoluble in the organic liquid, preferably wherein the solubility of the at least two quinacridone pigments and the inorganic salt in the organic liquid at a temperature in the range of 20-25° C. is in the range of 0-10 g / L, preferably 0.0001-9.5 g / L, more preferably 0.0005-9 g / L.

[0162] 12. The process according to any one of embodiments 1 to 11, wherein the particle size distribution Dv(50) is determined according to Reference Example 5.

[0163] 13. The process according to any one of embodiments 1 to 12, wherein the ground at least two quinacridone pigments have a particle size distribution Dv(50) determined according to Reference Example 5 in the range of 20-140 nm, preferably 25-130 nm, more preferably 30-120 nm.

[0164] 14. The method of any one of embodiments 1 to 13, wherein the mixed crystal quinacridone pigment composition has a particle size distribution Dv(50) of <150 nm as determined according to Reference Example 5, preferably the mixed crystal quinacridone pigment composition has a particle size distribution Dv(50) in the range of 10-145 nm, more preferably 20-140 nm, more preferably 25-130 nm, more preferably 30-120 nm.

[0165] 15. The method of any one of embodiments 1 to 14, wherein (a) further comprises grinding the crude quinacridone pigment in the presence of a diketopyrrolopyrrole selected from PR 264, PR 272, and mixtures thereof.

[0166] 16. The method of any one of embodiments 1 to 15, wherein the organic liquid is selected from diethylene glycol, glycerol, diacetone alcohol and a mixture of two or more thereof, preferably the organic liquid is diethylene glycol.

[0167] 17. The method of any one of embodiments 1 to 16, wherein the synergist in (a)(iii) is a quinacridone derivative selected from the group consisting of quinacridone sulfonic acid and its salts, phthalimidoalkyl-quinacridones, imidazolylalkyl-quinacridones, pyrazolylalkyl-quinacridones, sulfonic acids and salts of pyrazolylalkyl-quinacridones, dialkylaminoalkylsulfonamide derivatives of quinacridones, and mixtures of two or more thereof.

[0168] 18. The method of embodiment 17, wherein the quinacridone derivative is selected from the group consisting of sulfonic acid derivatives and / or salts of quinacridone; 5,7,12,14-tetrahydro-7,14-dioxoquinolino[2,3-b]acridine-2-sulfonic acid and its metal salts; the reaction product of formaldehyde with 5,12-dihydroquinolino[2,3-b]acridine-7,14-dione and 3,5-dimethyl-1H-pyrazole; The sulfonation reaction product of 5,12-dihydroquinolin-[2,3-b]acridine-7,14-dione and 3,5-dimethyl-1H-pyrazole or 2-[(1,3-dihydro-1,3-dioxo-2H-isoindol-2-yl)methyl]-5,12-dihydroquinolin-[2,3-b]acridine-7,14-dione and a mixture of two or more thereof, preferably the quinacridone derivative is a monosulfonic acid metal salt derivative of PV 19.

[0169] 19. The method of any one of embodiments 1 to 16, wherein the synergist in (a)(iii) is selected from natural or synthetic resins comprising esters and salts of abietic acid; hydrated or partially hydrogenated or dimerized rosins; polysorbate-type nonionic surfactants comprising esters or ester mixtures formed from fatty acids, preferably lauric acid or sebacic acid; polyols, preferably sorbitan monolaurate and dibutyl sebacate; and mixtures of two or more thereof.

[0170] 20. The method of any one of embodiments 1 to 19, wherein the synergist in (a)(iii) is present in an amount of 1 to 10 wt. %, based on the at least two quinacridone pigments in (a), preferably in an amount of 1 to 5 wt. %, based on the at least two quinacridone pigments in (a).

[0171] 21. The process of any one of embodiments 1 to 20, wherein the synergist in (a)(iii) is present in the range of 0.001 to 0.1 parts by weight based on the at least two quinacridone pigments in (a).

[0172] 22. The method of any one of embodiments 1 to 21, wherein the mixed crystal quinacridone pigment composition comprising the at least two quinacridone pigments has a particle size distribution Dv(50) determined according to Reference Example 5 in the range of 10-145 nm, preferably 20-140 nm, more preferably 25-130 nm, more preferably 30-120 nm.

[0173] 23. The method of any one of embodiments 1 to 22, wherein the mixed crystal quinacridone pigment composition is characterized by powder X-ray diffraction signals at diffraction angles 2θ of 5.9°±0.2° and 11.9°±0.2°.

[0174] 24. The method of embodiment 23, wherein the mixed crystal quinacridone pigment composition is further characterized by powder X-ray diffraction signals at diffraction angles 2θ of 8.0°±0.2° and 17.9°±0.2° after adding PR 264.

[0175] 25. The method of embodiment 23, wherein the mixed crystal quinacridone pigment composition is further characterized by powder X-ray diffraction signals at diffraction angles 2θ of 7.7°±0.2° and 15.7°±0.2° after adding PR 272.

[0176] 26. The process according to any one of embodiments 1 to 25, wherein the process comprises a one-step solvent-salt kneading process.

[0177] 27. A mixed crystal quinacridone pigment composition obtainable by or obtained from the method of any one of embodiments 1 to 26.

[0178] 28. A mixed crystal quinacridone pigment composition according to embodiment 27, wherein the ratio of the diffraction peak intensity at a diffraction angle 2θ of 5.9±0.2° to the diffraction peak intensity at a diffraction angle 2θ of 11.9±0.2°C is 3 or more as measured by a powder X-ray diffraction method, preferably the ratio of the diffraction peak intensity at a diffraction angle 2θ of 5.9±0.2° to the diffraction peak intensity at a diffraction angle 2θ of 11.9±0.2°C is in the range of 3-20, more preferably in the range of 6-10, and preferably the ratio of the diffraction peak intensities is measured according to Reference Example 4.

[0179] 29. The mixed crystal quinacridone pigment composition of embodiment 27 or 28, wherein the amount of the synergist is in the range of 0.1-10 parts by mass, preferably 0.5-3 parts by mass or 1-5 parts by mass, relative to 100 parts by mass of the mixed crystal quinacridone pigment composition.

[0180] 30. The mixed crystal quinacridone pigment composition according to any one of embodiments 27 to 29, wherein the particle size distribution Dv(50) is determined according to Reference Example 5 in the range of 10-145 nm, preferably 20-140 nm, more preferably 25-130 nm, more preferably 30-120 nm.

[0181] 31. The mixed crystal quinacridone pigment composition of any one of embodiments 27 to 30, wherein the composition is chlorine-free.

[0182] 32. A printing ink, coating or plastic composition comprising the mixed crystal quinacridone pigment composition of any one of embodiments 27 to 31.

[0183] 33. The printing ink or coating composition of embodiment 32, wherein the composition is suitable for use as a printing ink, an automotive coating, an architectural coating or an industrial coating.

[0184] 34. The printing ink composition of embodiment 32, wherein the composition is suitable for use as a digital printing ink, an inkjet ink, an electrophotographic toner, an aqueous ink, a UV curable ink, a solvent-based ink or an oil-based ink.

[0185] 35. A printed or coated article comprising the printing ink or coating composition of any one of embodiments 32-34.

[0186] 36. The printed article of embodiment 35, wherein the article is a plastic article.

[0187] 37. A plastic article comprising the mixed crystal quinacridone pigment composition of any one of embodiments 27-31.

[0188] The invention has been described in detail, including preferred embodiments thereof. However, it will be appreciated that those skilled in the art, upon consideration of this disclosure, may make variations and / or modifications to the invention that fall within the scope and spirit of the invention. Example

[0189] The present invention is further illustrated by the following non-limiting examples, which further illustrate the invention and are not intended, nor should they be construed, to limit the scope of the invention.

[0190] Example 1

[0191] 20.0 g of crude γ-PV 19 and 11.1 g of PR 122 were added to a kneading apparatus (twin blade kneader) with a capacity of 0.6 liters. 214.3 g of sodium chloride and 45.0 g of diethylene glycol (DEG) were added to the kneader. The walls of the apparatus were thermostated at 80° C. After 12 hours of kneading, 3.6 g of PR 264 and 1.1 g of the monosulfonic acid metal salt derivative of PV 19 were added and kneading was continued for 12 hours with the walls thermostated at 80° C. The kneading was then stopped, 1.6 L of water was added to the kneaded mass and stirred for 3 hours. The mixture was filtered and the pigment was washed with water until the conductivity of the filtrate was less than 100 μS / cm. The wet filter cake was dried in an oven at 80° C. for 24 hours. The yield of the pigment obtained was 34.1 g and contained 56% PV 19 and 31% PR 122 in mixed crystals as a physical mixture with 10% PR 264 and 3% of the monosulfonic acid metal salt derivative of PV 19. The pigment was comminuted in a mill to give a magenta powder.

[0192] Example 2

[0193] 21.7 g of crude γ-PV 19 and 9.3 g of PR 122 were added to a kneading apparatus (twin blade kneader) with a capacity of 0.6 liters. 214.3 g of sodium chloride and 45.0 g of diethylene glycol (DEG) were added to the kneader. The walls of the apparatus were thermostated at 80° C. After 12 hours of kneading, 3.6 g of PR 272 and 1.1 g of the monosulfonic acid metal salt derivative of PV 19 were added and kneading was continued for 12 hours with the walls thermostated at 80° C. The kneading was then stopped, 1.6 L of water were added to the kneaded mass and stirred for 3 hours. The mixture was filtered and the pigment was washed with water until the conductivity of the filtrate was less than 100 μS / cm. The wet filter cake was dried in an oven at 80° C. for 24 hours. The yield of the pigment obtained was 34.5 g and contained 61% PV 19 and 26% PR 122 in mixed crystals as a physical mixture with 10% PR 272 and 3% of the monosulfonic acid metal salt derivative of PV 19. The pigment was comminuted in a mill to give a magenta powder.

[0194] Example 3

[0195] 24.5 g of crude γ-PV 19 and 8.2 g of PR 122 were added to a kneading apparatus (twin blade kneader) with a capacity of 0.6 liters. 214.3 g of sodium chloride and 45.0 g of diethylene glycol (DEG) were added to the kneader. The walls of the apparatus were thermostated at 80° C. After 6 hours of kneading, 1.8 g of PR 272 and 1.1 g of the monosulfonic acid metal salt derivative of PV 19 were added and kneading was continued for 6 hours with the walls thermostated at 80° C. The kneading was then stopped, 1.6 L of water were added to the kneaded mass and stirred for 3 hours. The mixture was filtered and the pigment was washed with water until the conductivity of the filtrate was less than 100 μS / cm. The wet filter cake was dried in an oven at 80° C. for 24 hours. The yield of the pigment obtained was 34.5 g and contained 69% PV 19 and 23% PR 122 in mixed crystals as a physical mixture with 5% PR 272 and 3% of the monosulfonic acid metal salt derivative of PV 19. The pigment was comminuted in a mill to give a magenta powder.

[0196] Example 4

[0197] 20.7 g of crude γ-PV 19 and 11.4 g of PR 122 were added to a kneading apparatus (twin blade kneader) with a capacity of 0.6 liters. 214.3 g of sodium chloride and 45.0 g of diethylene glycol (DEG) were added to the kneader. The walls of the apparatus were thermostated at 80° C. After 12 hours of kneading, 3.6 g of PR 272 were added and kneading was continued for 12 hours with the walls thermostated at 75-80° C. The kneading was then stopped, 1.6 L of water were added to the kneaded mass and stirred for 3 hours. The mixture was filtered and the pigment was washed with water until the conductivity of the filtrate was less than 100 μS / cm. The wet filter cake was dried in an oven at 80° C. for 24 hours. The yield of the resulting pigment was 34.5 g and contained 58% of PV 19 and 32% of PR 122 in a mixed crystal as a physical mixture with 10% of PR 272. The pigment was pulverized in a mill to obtain a magenta powder.

[0198] Example 5

[0199] 20.7 g of crude γ-PV 19 and 11.4 g of PR 122 were added to a kneading apparatus (twin blade kneader) with a capacity of 0.6 liters. 214.3 g of sodium chloride and 45.0 g of diethylene glycol (DEG) were added to the kneader. The walls of the apparatus were thermostated at 76-80° C. After 12 hours of kneading, 3.6 g of PR 264 were added and kneading was continued for 12 hours with the walls thermostated at 76° C. The kneading was then stopped, 1.6 L of water were added to the kneaded mass and stirred for 3 hours. The mixture was filtered and the pigment was washed with water until the conductivity of the filtrate was less than 100 μS / cm. The wet filter cake was dried in an oven at 80° C. for 24 hours. The yield of the resulting pigment was 34.9 g and contained 58% of PV 19 and 32% of PR 122 in a mixed crystal as a physical mixture with 10% of PR 264. The pigment was pulverized in a mill to obtain a magenta powder.

[0200] Example 6

[0201] 25.1 g of crude γ-PV 19 and 8.4 g of PR 122 were added to a kneading apparatus (twin blade kneader) with a capacity of 0.6 liters. 214.3 g of sodium chloride and 45.0 g of diethylene glycol (DEG) were added to the kneader. The walls of the apparatus were thermostated at 80° C. After 6 hours of kneading, 1.8 g of PR 264 and 0.4 g of the monosulfonic acid metal salt derivative of PV 19 were added and kneading was continued for 6 hours with the walls thermostated at 80° C. The kneading was then stopped, 1.6 L of water were added to the kneaded mass and stirred for 3 hours. The mixture was filtered and the pigment was washed with water until the conductivity of the filtrate was less than 100 μS / cm. The wet filter cake was dried in an oven at 80° C. for 24 hours. The yield of the pigment obtained was 34.9 g and contained 70% PV 19 and 24% PR 122 in mixed crystals as a physical mixture with 5% PR 272 and 1% of the monosulfonic acid metal salt derivative of PV 19. The pigment was comminuted in a mill to give a magenta powder.

[0202] Example 7

[0203] 18.8 g of crude γ-PV 19 and 12.9 g of PR 122 were added to a kneading apparatus (twin blade kneader) with a capacity of 0.6 liters. 214.3 g of sodium chloride and 45.0 g of diethylene glycol (DEG) were added to the kneader. The walls of the apparatus were thermostated at 75° C. After 12 hours of kneading, 3.6 g of PR 272 and 0.4 g of the monosulfonic acid metal salt derivative of PV 19 were added and kneading was continued for 12 hours with the walls thermostated at 75° C. The kneading was then stopped, 1.6 L of water and 45 mL of 20% hydrochloric acid (aqueous solution) were added to the kneaded mass and stirred at 70° C. for 2 hours. The mixture was filtered and the pigment was washed with water until the conductivity of the filtrate was below 100 μS / cm and the pH was above 6. The wet filter cake was dried in an oven at 80° C. for 24 hours. The yield of the pigment obtained was 34.6 g and contained 53% PV 19 and 36% PR 122 in mixed crystals as a physical mixture with 10% PR 272 and 1% of the monosulfonic acid metal salt derivative of PV 19. The pigment was comminuted in a mill to give a magenta powder.

[0204] Example 8

[0205] 20.2 g of crude γ-PV 19 and 10.9 g of PR 122 were added to a kneading apparatus (twin blade kneader) with a capacity of 0.6 liters. 214.3 g of sodium chloride and 45.0 g of diethylene glycol (DEG) were added to the kneader. The walls of the apparatus were thermostated at 80° C. After 12 hours of kneading, 3.6 g of PR 272 and 1.1 g of the monosulfonic acid metal salt derivative of PV 19 were added and kneading was continued for 12 hours with the walls thermostated at 78° C. The kneading was then stopped, 1.6 L of water were added to the kneaded mass and stirred for 3 hours. The mixture was filtered and the pigment was washed with water until the conductivity of the filtrate was less than 100 μS / cm. The wet filter cake was dried in an oven at 80° C. for 24 hours. The yield of the pigment obtained was 34.5 g and contained 57% PV 19 and 30% PR 122 in mixed crystals as a physical mixture with 10% PR 272 and 3% PV 19 of the monosulfonic acid metal salt derivative. The pigment was comminuted in a mill to give a magenta powder.

[0206] Example 9

[0207] 367.5 g of crude γ-PV 19 and 157.5 g of PR 122 were added to a kneading apparatus (sigma paddle kneader) with a capacity of 10 liters. 3300 g of sodium chloride and 650 g of diethylene glycol (DEG) were added to the kneader. The walls of the apparatus were thermostated at 50° C. After 6 hours of kneading, 22.1 g of PR 264 and 5.5 g of the monosulfonic acid metal salt derivative of PV 19 were added and kneading was continued for 4 hours with the walls thermostated at 50° C. to ensure an internal temperature of 70° C. The kneading was then stopped and 5 liters of water were added to the kneaded mass. The mixture was stirred for 3 hours at room temperature. 7 liters of water and 140 g of 20% HCl (aqueous solution) were then added and stirring was continued at 80° C. for 2 hours. The mixture was filtered and the pigment was washed with water until the conductivity of the filtrate was below 100 μS / cm. The wet filter cake was dried in an oven at 80° C. for 20 hours. The yield of the pigment obtained was 500 g and contained 67% PV 19 and 28% PR 122 in mixed crystals as a physical mixture with 4% PR 264 and 1% of the monosulfonic acid metal salt derivative of PV 19. The pigment was comminuted in a mill to give a magenta powder.

[0208] Comparative Example 1

[0209] 26.8 g of crude γ-PV 19 and 8.9 g of PR 122 were added to a kneading apparatus (two-blade kneader) with a capacity of 0.6 liters. 214.3 g of sodium chloride and 45.0 g of diethylene glycol (DEG) were added to the kneader. The walls of the apparatus were thermostated at 80° C. and the mixture was kneaded for 12 hours. 1.6 liters of water were then added, the mixture was stirred for 3 hours and then filtered. The pigment was washed with water until the conductivity of the filtrate was less than 100 μS / cm. The wet filter cake was dried in an oven at 80° C. for 24 hours. The yield of the pigment obtained was 35.0 g and contained 75% PV 19 and 25% PR 122 in the mixed crystals. The pigment was comminuted in a mill to give a magenta powder.

[0210] Comparative Example 2

[0211] 25.9 g of crude γ-PV 19 and 8.7 g of PR 122 were added to a kneading apparatus (twin blade kneader) with a capacity of 0.6 liters. 214.3 g of sodium chloride and 45.0 g of diethylene glycol (DEG) were added to the kneader. The walls of the apparatus were thermostated at 80-83° C. and the mixture was kneaded for 6 hours. 1.1 g of the monosulfonic acid metal salt derivative of PV 19 were then added and kneading was continued for 6 hours with the walls thermostated at 83° C. 1.6 liters of water were then added, the mixture was stirred for 3 hours and then filtered. The pigment was washed with water until the conductivity of the filtrate was less than 100 μS / cm. The wet filter cake was dried in an oven at 80° C. for 24 hours. The yield of the resulting pigment was 33.2 g and contained 73% of PV 19 and 24% of PR 122 in a mixed crystal as a physical mixture with 3% of the monosulfonic acid metal salt derivative of PV 19. The pigment was pulverized in a mill to obtain a magenta powder.

[0212] Test Method

[0213] Color performance:

[0214] Preparation of 5 wt% Pigment Grind Base (Preparation 1)

[0215] A 5 wt% pigment grind base is prepared by combining 5 wt% of the pigment with 95 wt% of the oven dried alkyd based solvent based base test system in a sealable container. ) were added to the container at a weight ratio of 1:1.5 mill base component: beads, the container was loaded into a Skandex disperser and the mill base component was dispersed for 4 hours.

[0216] Preparation of 45 wt% Pigmentary Titanium Dioxide Mill Base (Preparation 2)

[0217] A 45 wt% white mill base is prepared by combining 45 wt% titanium dioxide pigment (e.g., Kronos 2310 supplied by Kronos International Inc.) with 55 wt% of the oven dried alkyd based solvent based base test system in a sealable container. A dispersion medium (e.g., glass beads) is added. ) were added to the container at a weight ratio of 1:1.5 mill base components: beads, the container was loaded into a Skandex disperser and the mill base components were dispersed for 1 hour.

[0218] Preparation of white diluted material (Preparation 3)

[0219] 50 wt % of 5 wt % pigment mill base (Preparation 1) and 50 wt % of 45 wt % pigment titanium dioxide mill base (Preparation 2) were mixed using a high speed mixer (e.g. Hauschild series DAC 800 FVZ) at 2000 min. -1 Mix at 40°C for 60 seconds to provide a 10:90 pigment:titanium dioxide white washdown.

[0220] Preparation of master palette (Preparation 4)

[0221] 5 wt% of the pigment mill base (Preparation 1) was hand knife coated onto a black and white contrast panel (eg Leneta 2A-3) using a 150 μm spiral coater. The coating was allowed to dry at room temperature for 20 minutes and then baked at 130°C for 30 minutes.

[0222] Preparation of white diluted material board (Preparation 5)

[0223] The white washdown (Preparation 3) was hand-draw coated onto a black and white contrast panel (eg Leneta 2A-3) using a 150 μm spiral coater. The coating was allowed to dry at room temperature for 20 minutes and then baked at 130°C for 30 minutes.

[0224] Evaluation of transparency (ddE) (Reference Example 1)

[0225] The colorimetric evaluation was performed according to the spectroscopic method (ISO 18314-1 (2015)) with exclusion of the specular component in d / 8° or 8° / d geometry. The transparency was determined using a master color plate (prepared according to Preparation 4) based on DIN 55988 using the colorimetric parameter scattering-dE. The difference in transparency between any of Examples 1 to 8 or Comparative Examples 1 and 2 and the reference material Cinquasia Magenta D 4570 is given as ddE. Cinquasia Magenta D 4570 was set as a reference because its color tone is close to the target color tone of the invention in question and helps to judge the performance of the invention compared to the prior art PV 19 / PR 122 mixed crystal (comparative example).

[0226] Evaluation of hue (dH) (Reference Example 2)

[0227] The term H (hue) as used herein refers to the hue in the L*C*H color space (also known as CIELAB) specified by the Commission Internationale de l'Eclairage. dH represents the difference in hue between two samples. Cinquasia Magenta D 4570 was set as a reference because its hue is close to the target hue of the invention in question and helps to judge the performance of the invention compared to the prior art PV 19 / PR 122 mixed crystal (comparative example).

[0228] The colorimetric evaluation was carried out according to the spectral method (ISO 18314-1 (2015)) using a white diluted plate (prepared according to Preparation 5) with d / 8° or 8° / d geometry including the specular component and excluding the 4% specular component calculated subsequently. The hue was determined according to ISO 11664-4 (2008) for illuminant D65 and a 10° standard observer after matching the shadow depth.

[0229] Evaluation of relative color strength (CS) (Reference Example 3)

[0230] Color strength CS was measured according to ISO 18314-2 (2015) using a white diluted plaque (Preparation 5) by iterative matching of the color depth to 1 / 3 shade depth. Relative color strength was evaluated for Cinquasia Magenta D4570, as its hue is close to the target hue of the invention in question and helps to judge the performance of the invention compared to the prior art PV 19 / PR 122 mixed crystal (comparative example).

[0231] The criteria used for evaluation are as follows.

[0232] O = Successfully met criteria

[0233] X = criteria not met

[0234] transparency:

[0235] The more negative the value, the more transparent it is:

[0236] O:ddE<-3.0

[0237] X:ddE>-3.0

[0238] Color Strength:

[0239] The higher the value, the higher the relative color intensity.

[0240] O: CS ≥ 75

[0241] X: CS<75

[0242] tone:

[0243] The more positive the dH value, the lighter or more yellowish the color tone.

[0244] O: dH ≥ -3

[0245] X: dH < -3

[0246] Method for measuring PXRD (powder X-ray diffraction) and evaluating peak intensity ratio (reference example 4)

[0247] PXRD was measured using a powder X-ray diffractometer (Rigaku's MiniFlex 600 or Bruker D8 Advance Series 2) using Cu Kα rays as an X-ray source. The scanning range (2θ) was set to 4°-35° 2θ.

[0248] The intensity ratio is defined by:

[0249] Intensity ratio = (diffraction peak intensity at a diffraction angle 2θ of about 5.9°) / (diffraction peak intensity at a diffraction angle 2θ of about 11.9°)

[0250] Criteria for forming mixed crystals of PR 19 and PR 122:

[0251] O: Intensity ratio>3

[0252] X: Strength ratio <3

[0253] Method for measuring particle size distribution (Dv) (Reference Example 5)

[0254] To prepare the dispersion, 25 g of pigment was added to a 400 ml glass jar containing a blend of 75 g of deionized water (37.5 g), isopropanol (4.5 g), diethylene glycol monobutyl ether (3.0 g) and a high molecular weight block copolymer dispersant solution (Disperbyk-190, 30.0 g from BYK-Chemie GmbH). The dispersant / pigment ratio was 0.48 (dry basis). The pigment was then pre-dispersed by mixing the resulting mixture at 5000 rpm over 5 minutes using a high-speed dispersor (Dispermat LC-230) equipped with a 30 mm sawtooth blade. 200 g of zirconium oxide beads (0.7-0.9 mm diameter) were then added to the glass jar and the pigment was dispersed for 4 hours using a dispersor DAS200 unit (Lau GmbH).

[0255] The resulting pigment dispersion was left to stand for 24 hours and then analyzed for particle size distribution by means of a dynamic light scattering method (Malvern Zetasizer from Malvern Instruments Ltd).

[0256] Test Results

[0257] Table 1

[0258] Example E CS dH Strength ratio Example 1 -16.6(O) 90.6(O) -1.3(O) 8.8(O) Example 2 -7.2(O) 83.4(O) 2.1(O) 8.4(O) Example 3 -8.9(O) 79.1(O) 0.1(O) 9.4(O) Example 4 -3.4(O) 78.7(O) 5(O) 8.5(O) Example 5 -9.7(O) 86.6(O) 0.8(O) 7.4(O) Example 6 -9(O) 76.5(O) -0.4(O) 8.8(O) Example 7 -7.9(O) 76.1(O) 1.6(O) 9.1(O) Example 8 -7.3(O) 85.4(O) 1.2(O) 6.3(O) Comparative Example 1 -5.4(O) 62.2(X) 0.4(O) 6.4(O) Comparative Example 2 -14(O) 74.9(X) -3.4(X) 6.2(O)

[0259] As shown in Table 1, Inventive Examples 1 to 8 satisfy all requirements (O) in terms of transparency, color strength and hue, and exhibit excellent color properties. In contrast, Comparative Examples 1 and 2 each fail to satisfy the target property (X) in at least one case in terms of transparency, color strength and hue.

[0260] Table 2

[0261]

[0262] W = weak, M = medium, S = strong

[0263] As shown in Table 2, Inventive Examples 1-8 exhibit X-ray diffraction signals characteristic of mixed crystals of PV 19 and PR 122. In addition, Table 2 shows that PR 264 and PR 272 are not incorporated into mixed crystals, but exist as a physical mixture, as confirmed by the appearance of X-ray diffraction signals characteristic of the crystal lattice of a single PR 264 or PR 272 component.

[0264] Table 3

[0265] Dv(10)[nm] Dv(50)[nm] Dv(90)[nm] Cinquasia Magenta D 4570 79.9 176 320 Example 9 49.6 77.9 165

[0266] As shown in Table 3, Inventive Example 9 exhibited a particle size distribution of Dv(50) <150 nm. This is in contrast to the reference sample Cinquasia Magenta D 4570 which exhibited Dv(50)>150 nm. The narrow particle size distribution of Inventive Example 9 is confirmed by the Dv(10), Dv(50) and Dv(90) values ​​compared to the values ​​obtained for the reference sample Cinquasia Magenta D 4570.

[0267] References:

[0268] -JP2019112534

[0269] -EP3786236A1

[0270] -EP3778784

[0271] -EP3533842

[0272] -US 7166158

[0273] -EP 3480264B1

[0274] - High Performance Pigments, ed. Hugh M. Smith, p. 296, Wiley-VCH

[0275] Verlag-GmbH, 2002, ISBN 3-527-30204-2

Claims

1. A method for preparing a mixed crystal quinacridone pigment composition, comprising a one-step solvent-salt kneading process, the method comprising the following steps: (a) grinding a crude quinacridone pigment at a temperature in the range of about 40-120°C or 60-90°C or 40-90°C or 80-90°C in the presence of: (i) an inorganic salt in the range of about 3 to 12 parts by weight relative to the crude quinacridone pigment; (ii) an organic liquid in which the crude quinacridone pigment and salt are substantially insoluble; and (iii) optionally, a quinacridone synergist; (b) discharging the crude quinacridone pigment from step (a) into water; thereby obtaining a water / pigment mixture; and (c) separating a quinacridone pigment having a particle size distribution Dv(50) <150 nm from the mixture.

2. The method of claim 1, wherein the composition comprises a combination of PV 19 and PR 122, preferably wherein the composition is a combination of PV 19 and PR 122.

3. The method of claim 2, further comprising a diketopyrrolopyrrole selected from PR 264, PR 272, or both in the range of 0.1-15 wt % or 1-15 wt % or 5-10 wt % based on the total composition.

4. The method of claim 2, wherein the PV 19 and PR 122 are present in a ratio of 60:40-85:15 or 60:40-75:

25.

5. The method of any preceding claim, wherein the mixed crystal quinacridone pigment composition has a particle size distribution Dv(50) <150 nm as determined according to Reference Example 5, preferably the mixed crystal quinacridone pigment composition has a particle size distribution Dv(50) in the range of 10-145 nm, more preferably 20-140 nm, more preferably 25-130 nm, more preferably 30-120 nm.

6. The method of any preceding claim, wherein (a) further comprises grinding the crude quinacridone pigment in the presence of a diketopyrrolopyrrole selected from the group consisting of PR 264, PR 272, and mixtures thereof.

7. The process of any preceding claim, wherein PV 19 is 5,12-dihydroquinolino[2,3-b]acridine-7,14-dione and / or PR 122 is 2,9-dimethyl-5,12-dihydroquinolino[2,3-b]acridine-7,14-dione and / or PR 264 is 3,6-di-biphenyl-4-yl-2,5-dihydropyrrolo[3,4-c]pyrrole-1,4-dione and / or PR 272 is 3,6-di(4-methylphenyl)-2,5-dihydropyrrolo[3,4-c]pyrrole-1,4-dione.

8. The process of any preceding claim, wherein the one-step solvent-salt kneading process is a solvent-salt kneading process.

9. The process of any preceding claim, wherein in (a) the crude quinacridone pigment comprises a pigment resulting from a synthesis of the quinacridone pigment, preferably a synthesis without a finishing step, wherein the finishing step preferably comprises a modification selected from the group consisting of particle size modification and surface modification.

10. The process of any preceding claim, wherein in (a) the temperature is in the range of 60-90°C, preferably 40-90°C, more preferably 80-90°C or the temperature is in the range of 45-100°C, preferably 50-90°C.

11. The process of any preceding claim, wherein in (a)(i) the inorganic salt is selected from the group consisting of alkali metal halides, alkali metal sulfates, alkaline earth metal halides, alkaline earth metal sulfates and mixtures of two or more thereof, preferably wherein the inorganic salt is selected from the group consisting of sodium chloride, sodium sulfate, anhydrous aluminum sulfate and mixtures of two or more thereof, more preferably wherein the inorganic salt is sodium chloride.

12. The process of any preceding claim, wherein the solubility of the crude quinacridone pigment and the salt in the organic liquid in (a)(ii) at a temperature in the range of 20-25°C is in the range of 0-10 g / L, preferably 0.0001-9.5 g / L, more preferably 0.0005-9 g / L.

13. The method of any preceding claim, wherein in (a)(ii) the salt comprises an inorganic salt.

14. The method of any preceding claim, wherein the mixed crystal quinacridone pigment composition comprises a quinacridone synergist, wherein 0-10% by weight of the mixed crystal quinacridone pigment composition consists of the quinacridone synergist.

15. The process of any preceding claim, wherein the particle size distribution Dv(50) is determined according to Reference Example 5.

16. The process of any preceding claim, wherein in (c) the quinacridone pigment has a particle size distribution Dv(50) determined according to Reference Example 5 in the range of 10-145 nm, preferably 20-140 nm, more preferably 25-130 nm, more preferably 30-120 nm.

17. A method according to any preceding claim, wherein in (a)(ii) the organic liquid comprises a solvent.

18. The process of any preceding claim, comprising a solvent selected from the group consisting of ethylene glycol, diethylene glycol, diacetone alcohol, dimethylformamide, glycerol, triethylene glycol, dipropylene glycol, ethylene glycol monobutyl ether, methyl ethyl ketone, cyclohexanone, dimethylacetamide, N-methylpyrrolidone, butyl acetate, glycerol triacetate, sulfolane, xylene, tetrahydrofuran, butanol, water, dimethyl sulfoxide and blends thereof, preferably the solvent is selected from the group consisting of ethylene glycol, diethylene glycol, diacetone alcohol, dimethylformamide, glycerol, triethylene glycol, dipropylene glycol, ethylene glycol monobutyl ether, methyl ethyl ketone, cyclohexanone, dimethylacetamide, N-methylpyrrolidone, butyl acetate, glycerol triacetate, sulfolane, xylene, tetrahydrofuran, dimethyl sulfoxide and mixtures of two or more thereof.

19. The method of claim 18, wherein the at least one solvent comprises one or more of diethylene glycol, diacetone alcohol and glycerol, preferably the solvent is diethylene glycol.

20. The method of any preceding claim, wherein the synergist is a quinacridone derivative selected from the group consisting of quinacridone sulfonic acid and its salts, phthalimidoalkyl-quinacridones, imidazolylalkyl-quinacridones, pyrazolylalkyl-quinacridones, sulfonic acids and salts of pyrazolylalkyl-quinacridones and dialkylaminoalkylsulfonamide derivatives of quinacridones.

21. The method of any preceding claim, wherein the synergist is selected from the group consisting of sulfonic acid derivatives and / or salts of quinacridone; 5,7,12,14-tetrahydro-7,14-dioxoquinolino[2,3-b]acridine-2-sulfonic acid and its metal salts; the reaction products of formaldehyde with 5,12-dihydroquinolino[2,3-b]acridine-7,14-dione and 3,5-dimethyl-1H-pyrazole; the reaction products of formaldehyde with 5,12-dihydroquinolino[2,3-b]acridine-7,14-dione and 3,5-dimethyl-1H-pyrazole; Sulfonation reaction products of H-pyrazole or 2-[(1,3-dihydro-1,3-dioxo-2H-isoindol-2-yl)methyl]-5,12-dihydroquinolino[2,3-b]acridine-7,14-dione; natural or synthetic resins containing esters and salts of abietic acid; hydrated or partially hydrogenated or dimerized rosin; polysorbate type nonionic surfactants containing esters or ester mixtures formed from fatty acids such as lauric acid or sebacic acid; polyols such as sorbitan monolaurate or dibutyl sebacate; and blends thereof.

22. The process of any preceding claim, wherein the synergist is present in an amount of 1-10 wt % relative to the crude quinacridone pigment, preferably the synergist in (a)(iii) is present in an amount of 1-10 wt % relative to the crude quinacridone pigment in (a).

23. The process of any preceding claim, wherein the synergist is present in an amount of 1-5 wt % relative to the crude quinacridone pigment, preferably the synergist in (a)(iii) is present in an amount of 1-5 wt % relative to the crude quinacridone pigment in (a).

24. The method of any preceding claim, wherein the synergist is present in the range of about 0.001-0.1 parts by weight relative to the crude quinacridone pigment, preferably the synergist in (a)(iii) is present in the range of about 0.001-0.1 parts by weight relative to the crude quinacridone pigment in (a).

25. The process of any preceding claim, wherein the narrow particle size distribution obtained with Dv(50) is <150 nm as determined according to Reference Example 5, preferably the narrow particle size distribution obtained with Dv(50) is in the range of 10-145 nm, more preferably 20-140 nm, more preferably 25-130 nm, more preferably 30-120 nm.

26. The method of any preceding claim, wherein the composition is characterized by a powder X-ray diffraction signal at diffraction angles 2θ of about 5.9°±0.2° and 11.9°±0.2°.

27. The method of claim 26, wherein the composition is further characterized by powder X-ray diffraction signals at diffraction angles of 8.0°±0.2° 2θ and 17.9°±0.2° 2θ after addition of PR 264.

28. The method of claim 26, wherein the composition is further characterized by powder X-ray diffraction signals at diffraction angles of 7.7°±0.2° 2θ and 15.7°±0.2° 2θ after addition of PR 272.

29. A mixed crystal quinacridone pigment composition obtained by the method of any one of claims 1 to 28.

30. The pigment composition of claim 29, wherein the ratio of the diffraction peak intensity at a diffraction angle 2θ of 5.9±0.2° to the diffraction peak intensity at a diffraction angle 2θ of 11.9±0.2°C is 3 or more as measured by a powder X-ray diffraction method, preferably the ratio of the diffraction peak intensity at a diffraction angle 2θ of 5.9±0.2° to the diffraction peak intensity at a diffraction angle 2θ of 11.9±0.2°C is in the range of 3 to 20, more preferably 6 to 10, and preferably the ratio of the diffraction peak intensities is measured according to Reference Example 4.

31. The pigment composition according to claim 29 or 30, wherein the content of the quinacridone pigment derivative is 0.1-10 parts by mass relative to 100 parts by mass of the pigment, and preferably the amount of the quinacridone pigment derivative contained in (a)(iii) is 0.1-10 parts by mass relative to 100 parts by mass of the mixed crystal quinacridone pigment composition.

32. The pigment composition according to claim 29 or 30, wherein the content of the quinacridone pigment derivative is 1 to 5 parts by mass relative to 100 parts by mass of the pigment, and preferably the amount of the quinacridone pigment derivative contained in (a)(iii) is 1 to 5 parts by mass relative to 100 parts by mass of the mixed crystal quinacridone pigment composition.

33. The pigment composition according to claim 29 or 30, wherein the content of the quinacridone pigment derivative is 0.5-3 parts by mass, preferably 1-3 parts by mass, relative to 100 parts by mass of the pigment, and preferably the amount of the quinacridone pigment derivative contained in (a)(iii) is 0.5-3 parts by mass, preferably 1-3 parts by mass, relative to 100 parts by mass of the mixed crystal quinacridone pigment composition.

34. The pigment composition according to any one of claims 29 to 33, wherein the narrow particle size distribution obtained as Dv(50) is determined according to Reference Example 5 to be <150 nm, preferably the narrow particle size distribution obtained as Dv(50) is in the range of 10-145 nm, more preferably 20-140 nm, more preferably 25-130 nm, more preferably 30-120 nm.

35. The pigment composition of any one of claims 29 to 34, wherein the composition is chlorine-free.

36. A printing ink or coating or plastic composition comprising the pigment composition of any one of claims 29 to 35.

37. The printing ink or coating composition of claim 36, wherein the composition is suitable for use as a printing ink, automotive coating, architectural coating or industrial coating.

38. The printing ink composition of claim 37, wherein the composition is suitable for use as a digital printing ink, an inkjet ink, an electrophotographic toner, an aqueous ink, a UV curable ink, a solvent-based ink, or an oil-based ink.

39. A printed or coated article comprising the printing ink or coating composition of any one of claims 35 to 38.

40. The printed article of claim 39, wherein the article is a plastic article.

41. A plastic article comprising the pigment composition of any one of claims 29 to 35.

Citation Information

Patent Citations

  • Transparent organic pigment high in tinting strength and preparation method thereof

    CN105885543A

  • Process for preparing quinacridones

    CN1154387A

  • Dyestuff compositions, its mfg. method, colouring pigment and colouring material

    CN1323857A

  • Crimson-coloured pigment composition and utilization thereof

    CN1354772A

  • Pigment for color filter, and coloring composition for color filter and color filter using the same

    JP2004258134A